Physiology of flowering in litchi (Litchi chinensis): A review - MALHOTRA, S K; SINGH, SANJAY KUMAR; NATH, VISHAL (The Indian Journal of Agricultural Sciences, 2018)
Lychee or litchi (Litchi chinensis Sonn.) is most popular fruit of South-East Asia, produces leaf flushes, flowers and fruits on terminals of new growth. The reproductive phase is associated with the ability to alternate between the production of vegetative and reproductive buds. The stress factors like water stress, cold winter are the triggering factors to induce dormancy which promotes flowering. The trees must experience one flush of vegetative growth during summer immediately after harvest and require a minimum number of three flushes for adequate fruit production. The flushes maturing earliest (before the winter period) produce floral shoots, while trees flushes maturing quite late produce vegetative shoots. The stem must take rest for 4 to 6 weeks prior to winter-spring flush for panicle formation in same flush. High leaf N is conducive for frequent flushes of vegetative growth and concentration less than 1.70 percent discourages initiation of vegetative flushes in the fall period. The vegetative flushing just prior to floral induction results in poor or no initiation and often vegetative shoots. The transition from vegetative to floral development is the consequence of changes in the physical and genetical expression in the shoot apex (with high cytokinin concentration). One month before flower bud formation, abscisic acid increases markedly and total cytokinin content increased in the xylem sap reaching maximum during flower bud formation and full bloom. The chlorophyll concentration dependent photosynthesis rate of lychee leaves on younger flushes and adjacent to fruit, is greater than that on shaded older flushes. The available total non structural carbohydrates or starch is found to be accumulated before flower initiation and leaf flushing. Girdling (generally done when post harvest flushes are matured) and spray of paclobutrazol (PBZ) and/or KNO3 induced flowering in China litchi.